Neutral endopeptidase inhibitor suppresses the early phase of atrial electrical remodeling in a canine rapid atrial pacing model - Imaki, Ryuta (Indian Heart Rhythm Society, 2008)
INTRODUCTION: We examined the acute effects of neutral endopeptidase inhibitor on the hemodynamics and electrical properties of dogs subjected to rapid atrial pacing. METHODS: Ten beagle dogs were used and divided into two groups with and without candoxatril, a neutral endopeptidase inhibitor preadministration. Before and after the 6 hours rapid atrial pacing from the right atrial appendage, the hemodynamics, atrial effective refractory period, and monophasic action potential duration of the right atrial appendage were measured and blood samples were collected. Atrial tissue was also excised after the experiment. RESULTS: Candoxatril significantly increased plasma ANP levels (Control: 88.4 ± 50.25 vs. Candoxatril: 197.1 ± 32.09 pg/ml, p = 0.004) and prevented reductions in atrial effective refractory period and monophasic action potential duration. We further demonstrated that the treated animals exhibited significantly higher levels of atrial tissue cyclic GMP (Control: 28.1 ± 1.60 fmol/mg vs. Candoxatril: 44.5 ± 12.28 fmol/mg, p = 0.034) as well as that of plasma cyclic GMP (Control: 32 ± 5.5 vs. Candoxatril: 42 ± 7.1 pg/ml, p = 0.028). CONCLUSION: Candoxatril suppressed the shortening of atrial effective refractory period and monophasic action potential duration in the rapid atrial pacing model. As plasma ANP and the atrial tissue levels of cyclic GMP were higher in the Candoxatril group than the control, this effect was considered to appear through the reduction of calcium overload caused by ANP and cyclic GMP.